ISLAMIC EDUCATION in INDONESIA DURING the DUTCH COLONIAL; The Case Muhammadiyah and NU - Ahmad Hijazi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
The hegemony of colonialism in the Muslim world, including in Indonesia, has produced complex problems. Since there is a restriction to religious activities, education was targeted to forbid. However, in Indonesia, this process could not be implemented by the Dutch government since the Muslim intellectuals did not want the process implemented. Indonesian Muslim intellectuals at that time tried to establish Islamic organizations as resuscitation media for Muslim societies. It is interesting that there is different spirit among Islamic organizations so it creates different character or model in resuscitating Muslim societies at that time.Islamic organizations such as Jamiat Khair, Persyarikatan Ulama, Muhamadiyah, and NU have different characteristics in making transformation in the society. In this case, different backgrounds of the founding fathers of the organization influence this difference. Also, the responses to the problems of Muslim societies were also different. Muhammadiyah which had basis in the towns and intellectual communities was different from NU which had followers in the villages who had mystical traditions.